The contribution of work engagement and job satisfaction to workers' Psychological well-being - Reno Chandra Liona; Muhammad Salis Yurniardi (Universitas Ahmad Dahlan, 2020)
Workers are assets to increase the productivity of the company. Workers who have a good level of psychological well-being will be able to optimize their potency and, eventually, to perform a high level of productivity. A growing body of literature suggested that work-engagement and job satisfaction may affect psychological well-being. Therefore, this study aimed to investigate the relative contribution made by work engagement and job satisfaction to the psychological well-being of workers. Two hundred and six-nine workers (43.9% male and 56.1% female) participated in this study, which implemented the quantitative correlational research method. Work engagement was measured using the UWES-17 (Utrecht Work Engagement Scale), job satisfaction by using The Job Satisfaction Survey, and psychological well-being using Ryff's Psychological Well-being Scales. The results from the linear regression analysis indicated that 41% of the variance could be explained by both work engagement and job satisfaction on the psychological well-being of workers. Work engagement and job satisfaction could create optimal psychological functioning and experience for workers, resulting in higher overall well-being. However, job satisfaction contributed independently to a slightly larger contribution (22.23%) than work-engagement did (18.86%). All in all, both work-engagement and job significantly satisfaction predicted the psychological well-being of workers.